Sustainable Islamic development and population needs - Nawruoz Ahmed Yassin (Islamic Sciences Journal, 2024)
ABSTRACT Housing need is expressed as the situation in which the housing stock is unable to provide the expected quality and quantity of housing units for residents in a place, regardless of their economic ability or desire to acquire housing units. Accordingly, housing need can be understood as the gap between the existing housing units and what is expected from these units in a certain period of time. The housing need can also be expressed as “the existing housing units are not sufficient to meet the housing need of families in terms of the required quantity and quality.” It can be added that the lack of housing units means the weakness of the housing sector, which represents one of the basic sectors of the national economy, and even one of the signs of economic backwardness in the country.